Myocardial Infarction Associated with Regional Myocardial Flow Deficit and Normal Coronary Arteries in a Patient with COVID-19: A Case Report - Money, Joel E; Sekaran, Nishant K; Minder, C Michael; Le, Viet T; Mason, Steve M; Muhlestein, Joseph B; Knowlton, Kirk U; Anderson, Jeffrey L (Cardiology and Cardiovascular Medicine, 2020)
Myocardial injury is increasingly recognized as a complication in patients with COVID-19, but the pathophysiological basis remains uncertain. Here we present a case of non-ST-segment elevation myocardial infarction associated with small vessel or microvascular dysfunction as determined by multimodality imaging in a patient with COVID-19.